2015
DOI: 10.1002/bit.25654
|View full text |Cite
|
Sign up to set email alerts
|

Silks as scaffolds for skin reconstruction

Abstract: In this short review, we describe the use of high molecular weight proteins produced in the glands of several arthropods-commonly called silks-for the purpose to enhance human skin wound healing. To this end an extensive literature search has been performed, the publications have been categorized concerning silk preparation and application and summarized accordingly: Scaffolds to promote wound healing were prepared by processing the silks in different ways including solubilization of the protein fibers followe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 19 publications
(56 reference statements)
0
21
0
Order By: Relevance
“…Meinel and colleagues showed that silk scaffolds promoted more extensive chondrogenesis compared to collagen scaffolds when seeded with human mesenchymal stem cells [96]. More recent efforts have used the combination of stem cells with silk scaffolds to engineer skin as reviewed recently [101]. Silk offers superior biocompatibility in comparison to other biomaterials based on in vivo testing.…”
Section: Silkmentioning
confidence: 99%
“…Meinel and colleagues showed that silk scaffolds promoted more extensive chondrogenesis compared to collagen scaffolds when seeded with human mesenchymal stem cells [96]. More recent efforts have used the combination of stem cells with silk scaffolds to engineer skin as reviewed recently [101]. Silk offers superior biocompatibility in comparison to other biomaterials based on in vivo testing.…”
Section: Silkmentioning
confidence: 99%
“…Silk is another natural biomaterial with slow degradation rate, suitable for skin tissue engineering, that can be obtained from either Bombyx mori cocoons or Nephila silk glands . They can be used to make silk films, foams as well as woven or nonwoven scaffolds.…”
Section: Natural Biomaterialsmentioning
confidence: 99%
“…Many arthropods, such as spiders and silkworms produce silks in the epithelial cells of their specialized glands which are basically proteins having highly repetitive sequence, consisting mainly of glycine (43%), alanine (30%), and serine (12%) -[GAGSGA]n motifs, arranged in -sheets regions embedded in an amorphous matrix [14,3] and confer high toughness and elasticity [2,4]. Silk of Bombyx mori silkworms contain two major protein components; fibroin and sericin.…”
Section: Silk Fibroin At a Glance:-mentioning
confidence: 99%
“…Silk fibroins have been successfully utilized for skin tissue engineering and wound healing applications for their high mechanical resistance, enzymatic-driven biodegradability and favorable cell attachment. Bombyx mori silkworm-derived fibroins are acquired from cocoon and separated from sericin by degumming in alkaline boiling water and following solubilization in hot LiBr solution [14,3]. Upon modification of the helical chain arrangements into -sheets via alcohol treatment or water vapor annealing, the regenerated silk water soluble form, silk I, can be converted into insoluble silk II [15].…”
Section: Silk Fibroin At a Glance:-mentioning
confidence: 99%